Distribución de «varillales» y «chamizales» en la zona reservada Allpahuayo Mishana (zram) utilizando imagen digital del satélite Landsat tm. - Gómez, Darwin (2006)
The objective has been to characterize the Amazon vegetation by reflectance value in satellite image and correlating with land surface. The Landsat TM satellite image is of September 2000 and field work has been realized in September 2001, the Amazon vegetation does not change in one year. For precision we use the GPS, the results in Landsat TM satellite image showed the «varillares» and «chamizales» correlated with GPS points.